A delicate balance : prioritising South Africa's energy resources - Crompton, Rod; Hofmeyr, Katherine (London : Wits Business School, 2019)
The case centres on the implementation of a new Integrated Resource Plan (IRP) by South Africa's department of energy aimed at decarbonising much of the South African economy. The energy Intensive Users Group, a collection of South African companies working in energy intensive sectors such as mining and manufacturing must create a response that both supports its members' need for electricity with the realities of global warming and pressure to reduce consumption of fossil fuels.
Originally Published In Crompton, R., & Hofmeyr, K. (2019). A Delicate Balance: Prioritising South Africa's Energy Resources. WBS-2019-8. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; South Africa. -- Department of Energy; Energy industries -- Environmental aspects -- South Africa -- Case studies